MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK SMP MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER - Berliana Amelia Yunita (Jurnal Edukasi dan Penelitian Matematika, 2020)
The first objective of learning mathematics is understanding mathematical concept. Based on observations in class VII SMPN 31 Padang in the 2019/2010 Academic Year, it was found that student’s understanding of mathematical concept was still low. This can be seen from the completeness of the scores for the daily test and Odd Semester End Test of students. Therefore, we need a learning model that can overcome these problems.  One of which learning model that can improve student’s mathematical concepts understanding is the Numbered Heads Together cooperative learning model. The purpose of this research is to describe theoretically how the NHT model can improve student’s understanding of mathematical concepts. This type of research is a literature study on improving understanding of mathematical concepts through the NHT model. The conclusion of this study is that the application of the type of NHT cooperative learning described in the related article regarding indicators on these abilities has a tendency to increase student’s understanding of mathematical concepts. Keywords__NHT, Cooperative Learning, Understanding Of Mathematical Consepts